Analysis of the Hadith on the Prohibition of Hoarding Goods (Ihtikar) and Its Relevance to the Bangkinang City Traditional Market - Paisal, Paisal; Hidayat, Hidayat (General Multidisciplinary Research Journal, 2025)
Introduction:This study examines the Hadith on the prohibition of hoarding goods (ihtikar) and its relevance to economic practices in the traditional market, particularly in Pasar Bawah Bangkinang Kota. The issue of ihtikar is highly significant because hoarding goods can disrupt market balance, cause artificial scarcity, and harm consumers, especially those from lower-income groups. Islamic teachings emphasize justice and fairness in economic transactions, and the prohibition of ihtikar serves as an ethical and moral guideline to prevent exploitation in trade. Methods:This research employs a qualitative approach using the library research method. The data were collected from classical and contemporary Islamic literature, including Hadith compilations, interpretations by scholars, and economic fiqh books. The collected data were analyzed through descriptive and content analysis techniques to understand the textual meaning of the Hadith and its contextual relevance to modern market conditions. Results:The findings reveal that the Hadith strongly condemns the act of hoarding goods for profit during times of scarcity, as it leads to market distortion and violates Islamic principles of justice and social responsibility. The moral values contained in the Hadith encourage market fairness, price stability, and protection of public welfare. Conclusion and Suggestion: The study concludes that the Hadith on ihtikar provides timeless guidance in regulating fair economic behavior and maintaining market stability. The values embedded in the Hadith should be internalized by traders, consumers, and policymakers to prevent unethical practices and promote social welfare. It is suggested that local authorities and religious leaders work collaboratively to promote awareness of Islamic business ethics, ensuring that traditional markets like Pasar Bawah Bangkinang Kota operate based on justice, transparency, and community well-being.